Budget Deficiency and Its Treatment Prospects and Policies with Reference to Iraq (2003-2012) - سالم, سالم عبد الحسين (Journal of Economics and Administrative Sciences, 2012)
Developed and underdevelopment countries, on equal terms, face the problem of budget deficiency. Budget deficiency means that the public expenditure surpasses the public revenues. This, on the international level, is one of the most serious economic problems with many direct effects on the national economy, and depends, basically, on its finance chosen method. Looking for a solution to this problem, for this reason and many other ones, has been highlighted in spite of the many attempts to reduce the role of the governmental expenditure. Budget deficiency can not be attributed to a single unique cause since it is complex phenomenons the causes of which are related to many factors contribute to its occurrence, some of which refer to the public expenditure, others to the public revenue. This deficiency in the under developing countries, in general, including Iraq is related, apparently, to oil produced quantity, its world prices, in addition to its relation to public expenditure and its structure. Treating this phenomenon, of course, follows its causes. Therefore, this paper focuses on the axes of public expenditure and revenues, and highlighted many prospects and polices adopted by this paper.